Purchase intention for green cars among Chinese millennials: Merging the Value–Attitude–Behavior theory and theory of Planned Behavior - Wang, Lei; Zhang, Qi; Wong, Philip, P. W. * (Frontiers Media, 2022)
The value–attitude–behavior and the theory of planned behavior (TPB) appear to provide limited explanation for consumer green purchase behavior. This study aims to examine the relationship between pro-environmental value, consumption value, and TPB toward green car purchasing intention among the young Chinese generation. A total of 541 student responses were collected, and the results showed that altruistic value positively influenced subjective norm (SN) and perceived behavioral control (PBC), but negatively influenced green purchase attitude (GPA). Biospheric value positively influenced GPA and PBC. Function value and emotional value positively influenced GPA, respectively, and emotional value fully mediated the relationship between function value and GPA. Furthermore, GPA, SN, PBC positively influenced intention toward green car purchasing behavior, respectively, and SN mediated the relationship between GPA and intention. This study shows how pro-environmental value and consumption value can influence components of TPB in green car purchase intention.